O papel da tecnologia digital na escalabilidade de inovações sociais - Mignoni, Julhete (Universidade do Vale do Rio dos Sinos, 2022)
Currently, one of the greatest challenges for humanity is the resolution of social and environmental problems. In such a provider scenario, institutions can function as organizations and protectors of society. Given this context, social innovation is a subject that has been attracting the attention of public institutions for its potential for social transformation. Criticism of innovative solutions increases the lack of timely initiatives and the difficulty of expanding them. However, the scalability of social innovations is a little explored issue. Among the alternatives that have been used recently to scale the impact of social innovations is the use of digital technology. However, the problem of how digital technologies can act as drivers of social innovation is also something that still needs to be studied. Given this issue and context, the present investigation is a multiple case study that seeks to understand how digital technologies contribute to the scalability of social innovations. Therefore, three cases of social innovation were selected: Food to Save, Cheap Food and Trashin. The study contributes to the identification of a new connection between the three scaling processes: scaling up and scaling deep processes enable and drive the scaling out process. This study also showed that digital technologies contribute to the scalability of social innovations in different aspects, including operationalizing initiatives, strengthening trust in the initiative and building relationships and engaging the network of actors. Still, there are contributions regarding the barriers and opportunities for the scalability of social innovations through digital technologies. Finally, this dissertation expanded the knowledge of how technology contributes to the scalability of social innovations. It is expected that its results, contributions and limitations generate reflections on the importance of establishing a digital infrastructure that favors the performance of initiatives that aim to solve societal challenges.
Keywords: Inovação social; Escalabilidade; Tecnologias digitais; Social innovation; Scalability; Digital technologies; ACCNPQ::Ciências Sociais Aplicadas::Administração